Sistem Pendukung Keputusan Menentukan Kenaikan Jabatan Pegawai Kantor Kejaksaan Negeri Pematangsiantar Menggunakan Metode PROMETHEE - Muhammad Ifnu Suhada; Irfan Sudahri Damanik; Ilham Syahputra Saragih; Sundari Retno Andani; Hasudungan Siahaan (STMIK Budi Darma, 2021)
Pematangsiantar District Attorney's Office is a government agency that is engaged in the management of law and human rights. Employees are very important resources to determine the success of a work unit. Efforts to improve the quality of performance of a civil servant is a promotion. Position is a position that indicates the level of a person of the State Civil Apparatus. Promotion is an award given for work performance and service of the State Civil Apparatus. Decision Support System (SPK) which can help make it easier to determine an employee can be said to be eligible for promotion. In this study the decision-making calculation method used is Promethee with 5 criteria namely rank, Education, Discipline, Position History, Test Results. The system was built using the PHP programming language. The test results using the Questionnaire Testing show that the system can function according to the needs of users and the system is declared to have fulfilled the criteria for structural promotion of Employees at Pematangsiantar District Attorney's Office.